Numerical modeling of the semi-elliptical fatigue crack growth using damage accumulation approach - Guchinsky, Ruslan Valerievich; Petinov, Sergey Vladimirovich (Computational Continuum Mechanics, 2015)
At present the modeling of surface fatigue crack growth for residual life assessment of structural elements is almost entirely based on the application of the Linear Elastic Fracture Mechanics (LEFM). Generally, it is assumed that the crack front does not essentially change its shape, which is not always confirmed by experiment. Furthermore, the LEFM approach cannot be applied when the stress singularity vanishes due to material plasticity, one of the leading factors associated with the material degradation and fracture. Also, the evaluation of stress intensity factors (SIF) meets difficulties associated with changes in the stress state along the crack front circumference. An approach is proposed for modeling the evolution of surface cracks based on the strain-life criterion for fatigue failure and the finite element modeling of damage accumulation. The generalized cyclic stress-strain curve is used for the elastic-plastic material response. The approach takes into account the nonlinear character of damage accumulation and an increase in the material compliance due to damage growth. A procedure is proposed to calculate a crack closure parameter at different crack front points for 3D problem under the assumption that a crack opens at each front point when its stress becomes positive. The damage accumulation technique was applied to model the propagation of a semi-elliptical crack from an initial defect in the steel compact specimen. Crack evolution modeling in the LEFM format was carried out for comparison. It is shown that the crack front stabilizes after some starting stage when a crack grows from different initial defects, and therefore the crack front evolution is practically independent of the initial crack shape for the given loading conditions. The results of simulation are in good agreement with the experimental data.